Valuation of EAFM Indicators in Raja ampat and Aru Islands Districts - mulyana1, mulyana (Universitas Djuanda Bogor, 2018)
EAFM implementation need indicators that could be used as tools of Â monotoring and evaluation about to what extent a fisheries Â management has been aplicated the principles of ecosystem-based management.Â Â The aim of study of EAFM indicators valuation is to evaluate theÂ perform of fisheries resources management with approach ofÂ EAFM indicators in Raja Ampat and Aru Islands Districts. EAFM indicators include 6 domains that are : (1) fish resources, (2) habitat and ecosystem, (3) fishing techniques, (4) Economy, (5) Social, and (6) institusional. Methods of Â data taking was carried out with Â survey method by means of interview/questionnaires and FGD (Foccus Group Discussion). Determination of samples quantity use purposive sampling. The evaluation result against domains of EAFM in Raja Ampat District ranged between 48.3 â 80.0.Â This is indicate that status of ecosystem-based region management in Raja Ampat District belonging in category noderate till excelent. The evaluation result against domains of EAFM in Aru Islands District ranged between 57.2 â 93.3.Â This is indicate that status of ecosystem-based region management in Aru Islands District belonging in category m oderate till excelent.Â Key words: EAFM, indicators, Raja Ampat, Aru Islands